Юридичні гарантії правоохоронної діяльності підрозділів боротьби з кіберзлочинністю МВС України - Марков, В. В.; Markov, V. V.; ORCID: http://orcid.org/0000-0003-2024-657X (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 2 (69). - С. 80-89., 2015)
З метою визначення поняття юридичних гарантій правоохоронної діяльності підрозділів боротьби з кіберзлочинністю МВС України розкрито сутність, значення та зміст юридичних гарантій правоохоронної діяльності вказаних суб’єктів. На підставі аналізу українського законодавства та узагальнення думок науковців юридичні гарантії правоохоронної діяльності підрозділів боротьби з кіберзлочинністю визначено як сукупність юридичних засобів (норм та інститутів), за допомогою яких такі суб’єкти реалізують свої завдання і функції. Зроблено висновок, що підрозділи боротьби з кіберзлочинністю МВС України зможуть ефективно реалізувати свої завдання лише за умови забезпечення всього комплексу юридичних гарантій їх правоохоронної діяльності.

In order to determine the definition of legal guarantees of law enforcement activity of cybercrime combating divisions of the Ministry of Internal Affairs of Ukraine the author has revealed the essence, significance and content of legal guarantees of law enforcement activity of the stated subjects. Based on the analysis of Ukrainian legislation and generalization of scholars’ thoughts the legal guarantees of law enforcement activity of cybercrime combating divisions are defined as the combination of legal means and (norms and institutions) with the assistance of which these subjects realize their tasks and functions. The types of such guarantees are regulatory (norms-principles, norms that consolidate means and measures of cybercrime combating: means of preventing, detecting, termination and investigation of crimes within cyberspace, legal liability for such crimes and mechanisms of bringing to it, norms that consolidate the rights and duties of cybercrime combating divisions; norms consolidating the measures of protecting officers of law enforcement agencies from interfering with the fulfillment of duties and realizing the rights according to the law; norms regulating their legal liability) and organizational ones. It is concluded that cybercrime combating divisions of the Ministry of Internal Affairs of Ukraine will be able to function effectively only if the whole complex of legal guarantees of their law enforcement activity is ensured.

С целью определения понятия юридических гарантий правоохранительной деятельности подразделений борьбы с киберпреступностью МВД Украины раскрыты сущность, значение и содержание юридических гарантий правоохранительной деятельности указанных субъектов. На основании анализа украинского законодательства и обобщения мнений учёных юридические гарантии правоохранительной деятельности подразделений борьбы с киберпреступностью определены как совокупность юридических средств (норм и институтов), с помощью которых такие субъекты реализуют свои задания и функции. Сделан вывод, что подразделения борьбы с киберпреступностью МВД Украины смогут эффективно реализовать свои задания лишь при условии обеспечения всего комплекса юридических гарантий их правоохранительной деятельности.
Markov, V.V. (2015), “Legal guarantees of law enforcement activity of cybercrime combating divisions of the Ministry of Internal Affairs of Ukraine”, [“Yurydychni harantii pravookhoronnoi diialnosti pidrozdiliv borotby z kiberzlochynnistiu MVS Ukrainy”], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 2, pp. 80-89.
Марков, В. В. Юридичні гарантії правоохоронної діяльності підрозділів боротьби з кіберзлочинністю МВС України // Вісник Харківського національного університету внутрішніх справ. - 2015. - № 2 (69). - С. 80-89.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; підрозділи боротьби з кіберзлочинністю; cybercrime combating divisions; подразделения борьбы с киберпреступностью; Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; боротьба з кіберзлочинністю; юридичні гарантії правоохоронної діяльності; борьба с киберпреступностью; юридические гарантии правоохранительной деятельности; combating cybercrime; legal guarantees of law enforcement activity